984: Some Letters to and by Gerbert d’Aurillac Dealing with “Arabic” Mathematics and Astronomy (Transmediterranean History, 2021)
In 984, Gerbert d’Aurillac exchanged three letters with fellow churchmen, which mention manuscripts dealing with arithmetic and astronomy. On this basis, this contribution traces a broader transfer of mathematical and astronomical knowledge from the Arabic-Islamic to the Latin-Christian sphere in the late- tenth century. Addressing the so-called “dark legend” of Gerbert, the earliest corpus of Latin works on the astrolabe, the abacus, and Hindu-Arabic numerals, as well as evidence for exchange between scholarly milieus in Umayyad al-Andalus and Catalonia, it discusses Gerbert’s direct involvement in this transfer.
Keywords: al-Andalus; artes liberales; knowledge transfer; teaching; translation; mathematics; astronomy; Hindu-Arabic numerals; Umayyads; astrolabe